2013
DOI: 10.4155/fmc.13.96
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Applications of Rna Cap Analogs

Abstract: Cap analogs are chemically modified derivatives of the unique cap structure present at the 5´ end of all eukaryotic mRNAs and several non-coding RNAs. Until recently, cap analogs have served primarily as tools in the study of RNA metabolism. Continuing advances in our understanding of cap biological functions (including RNA stabilization, pre-mRNA splicing, initiation of mRNA translation, as well as cellular transport of mRNAs and snRNAs) and the consequences of the disruption of these processes - resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 165 publications
2
67
0
1
Order By: Relevance
“…The 5'-cap of mRNA has been reported to be associated with mRNA transcription and translation, preventing the degradation of mRNA precursors, and serving as a binding site for regulatory factors, therefore, being involved in various RNA metabolic processes (3). By binding to the 5'-cap of mRNA, eIF4E forms a translation initiation complex involved in protein trafficking and translation, thereby regulating gene expression (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The 5'-cap of mRNA has been reported to be associated with mRNA transcription and translation, preventing the degradation of mRNA precursors, and serving as a binding site for regulatory factors, therefore, being involved in various RNA metabolic processes (3). By binding to the 5'-cap of mRNA, eIF4E forms a translation initiation complex involved in protein trafficking and translation, thereby regulating gene expression (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The cap plays a crucial role in several cellular processes, such as pre-mRNA splicing (Sharp 1994), transport of RNA from the nucleus to the cytoplasm (Lewis and Izaurralde 1997), protection of mRNA against degradation (Rhoads 1985), and translation initiation (Gingras et al 1999). Over the years, chemically modified cap analogs have been used for biochemical, biophysical, and structural studies on mechanisms of the aforementioned processes (Niedzwiecka et al 2002;Grudzien et al 2004;Jankowska-Anyszka et al 2011;Ziemniak et al 2013). So far, some of the most intense research directed toward the application of synthetic cap analogs has been focused on designing translation inhibitors that prevent binding of mRNA to eIF4E.…”
Section: All Cellular Eukaryotic Mrnas Have At Theirmentioning
confidence: 99%
“…It was shown that elements such as (1) the positive charge of the imidazole ring of guanosine, (2) the presence of at least two negative charges (or a negative charge and the free electron pair) within the phosphate chain, and (3) the presence of at least one hydrogen atom on the amino group of the 7-methyloguanosine should be preserved in order to synthesize an efficient translation inhibitor. To date, numerous modified cap analogs have been tested as inhibitors of cap-dependent translation in vitro by competing with mRNA for the binding site of eIF4E (Cai et al 1999;Grudzien et al 2004;Ghosh et al 2005;Jia et al 2010;Piecyk et al 2012;Ziemniak et al 2013). Unfortunately, due to their charged nature, in vivo application of such analogs is strictly limited.…”
Section: All Cellular Eukaryotic Mrnas Have At Theirmentioning
confidence: 99%
“…A major obstacle to understanding cap recognition by Dcp2 is that all previously studied m 7 GpppN cap analogs bind the enzyme with very weak (millimolar) affinities. We have previously identified several phosphate-modified cap analogs which, after incorporation at the 5 ′ terminus of mRNAs, make them more resistant to Dcp2-mediated decapping (GrudzienNogalska et al 2013;Ziemniak et al 2013a). The modifications include bridging substitution at the α/β-position of the cap (O-to-CH 2 or methylenebisphosphonate; O-to-NH or imidodiphosphate) (Grudzien et al 2006;Su et al 2011) or nonbridging substitution at the β-phosphate (O-to-S or phosphorothioate; O-to-BH 3 or boranophosphate) (Supplemental Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the analogs that made mRNA resistant to Dcp2 also bound the translational cap-binding protein eIF4E with higher affinity and, consequently, produced mRNA with both increased cellular half-life and increased translational efficiency. These cap-modified transcripts have found application in experimental mRNA-based therapies (Kuhn et al 2010;Ziemniak et al 2013a;Sahin et al 2014). …”
Section: Introductionmentioning
confidence: 99%